TI_GERICHTE 12.2019.121 vom 12. Dezember 2019 , Provvedimento cautelare - società anonima - nullità dell'assemblea generale - TI Tribunale d'appello (2019)
Provvedimento cautelare - società anonima - nullità dell'assemblea generale